KEPASTIAN HUKUM SERTIFIKAT HAK MILIK ATAS TANAH SEBAGAI BUKTI KEPEMILIKAN BIDANG TANAH - Dwi Satya Permana, I Gusti Agung; Sandi Sudarsana, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014)
Land is one of the most fundamental human needs. The background of this paperis there’s no legal guarantee of land ownership rights. There are so many land disputearising caused location and boundaries which is not proper with reality for example isoverlapping title deed. title deed is a copy of land book and letter of land size afterbecoming one title deed with a letter of paper cover that the set arrange by MinisterRegulation. This research aims to understand the title deed as a proof as well asverification of land rights. Method in this paper using normative method by analyzinggovernment regulation together with literature. Based on the number of land cases, itcan prove how importance a title deed as a proof of land ownership rights. Propertyrights of land will be attached to it owner along the owner does not waive or transfer itright.
Keywords: legal security, property rights, land